Living to 100 years and beyond: Drivers and implications. Issue 1 (April 2018) - Leeson, George W.
The world is ageing, both at an individual and a population level, and population ageing is truly a global phenomenon. The emergence of large numbers of centenarians has accompanied this development and the twenty-first century promises to be the century of centenarians. The number of centenarians in Europe increased from around 57, 000 in 2006 to almost 90, 000 in 2011. By 2100 the number is expected to reach around 1.4 million in England and Wales alone. This century of centenarians will be challenging in both the developed and the emerging economies. The trend has fundamental consequences for the way in which individuals view and live these ever-extending lives, but also for the way in which societal infrastructures (education, workplaces, housing, transport, and health and social care) will need to be adapted to the needs of extreme-aged populations. More importantly, perhaps, our perception of old age needs a dramatic reappraisal.